Bone mineralization in rhythmic gymnasts entering puberty: Associations with jumping performance and body composition variables - Võsoberg, K.; Tillmann, V.; Tamm, A.-L.; Maasalu, K.; Jürimäe, J. (Journal of Sports Science & Medicine, 2017)
This study examined bone mineral density (BMD) accrual in prepubertal rhythmic gymnasts entering puberty and their age-matched untrained control girls, and associations with baseline jumping performance and body composition over the 3-year period. Whole body (WB) and femoral neck (FN) BMD, WB fat mass (FM) and fat free mass (FFM), countermovement jump (CMJ) and rebound jumps for 15 s (RJ15s) were assessed in 25 rhythmic gymnasts and 25 untrained controls at baseline and after 3-year period. The changes over this period were calculated ( scores). Pubertal maturation over the 3-year period was slower in rhythmic gymnasts compared to untrained controls, while no difference in bone age development was seen. WB BMD increased similarly in both groups, while the increase in FN BMD was higher in rhythmic gymnasts compared with untrained controls. In rhythmic gymnasts, baseline FFM was the most significant predictor of WB BMD explaining 19.2% of the variability, while baseline RJ15s was the most significant predictor of FN BMD explaining 18.5% of the variability. In untrained controls, baseline FM explained 51.8 and 18.9% of the variability in WB BMD and FN BMD, respectively. In conclusion, mechanical loading of high-intensity athletic activity had beneficial effect on BMD accrual in rhythmic gymnasts and may have counterbalanced such negative factors on bone development as slower pubertal maturation and lower body FM. Baseline FFM and repeated jumps test performance were related to BMD accrual in rhythmic gymnasts, while baseline FM was related to BMD accrual in untrained controls